Numerical Hydromagnetic Thermal Mechanism in Chemically Reacting Fluid Over a Radiative Melting UPHSR With Resistive Heating - M. Alharbi, Khalid Abdulkhaliq; Adnan,; Tag-Eldin, Elsayed; F. Yassen, Mansour; Ahmed, Naveed; Khan, Umar (Frontiers in Physics, 2022)
The heat transport over an Upper Paraboloid Horizontal Surface of Revolution (UPHSR) is significant and gained much interest of the researchers and aero dynamists. The flow of fluid around the pointed surface of rocket, bullets, bonnet and fighting aircrafts exhibits such flows in which engineering parameters like shear stresses and Nusselt number significantly contributed. Therefore, the study of fluid comprising heat generation/absorption, Lorentz forces and chemical reaction over a radiative UPHSR is conducted. The basic constitutive relations transformed in dimensionless version via similarity variables and tackled numerically. The temperature β(η) extensively intensifies under stronger dissipation effects (Ec). Furthermore, Prandtl, Biot and thermal radiations effects are noticed of huge significance in the analysis of heat transfer. The concentration of the fluid decays for optimum Sc and γ over an Upper Paraboloid Horizontal Surface of Revolution (UPHSR). The local rate of mass (-ϕ'(0)) and temperature (-β'(0)) effectively increases for Bi and Sc, respectively.